Pendidikan Agama Islam di Perguruan Tinggi Keagamaan: Posisi Kelembagaan, Tantangan dan Strategi Pembelajaran - Nur Hakim; Rahmat Haryadi (ISEDU : Islamic Education Journal, 2025)
The purpose of this study was to analyze the institution of Islamic Religious Education (PAI) in Islamic religious universities (PTKI), identify the actual challenges faced, and explore learning strategies that are relevant to the needs of students. Normatively, PAI in PTKI has a strategic position in strengthening the religious character of students and the development of integration of Science and religion. However, there is a gap between the ideality of institutional vision and implementation at the learning level, especially in the face of globalization, academic secularism, and the tendency of religious exclusivism. This study uses a qualitative approach to the type of library studies (library research), utilizing secondary data in the form of Pai institutional documents at PTKI, previous research, and the latest academic literature. Data mining techniques are carried out through the study of documents, while data analysis uses in-depth analytical descriptive methods. The results showed that Pai institutions in PTKI faced epistemological stagnation and methodological rigidity. Effective learning strategies include contextual, integrative, dialogical, and moderate approaches that emphasize Islamic literacy towards contemporary social reality. This finding confirms the importance of institutional revitalization and pedagogical innovation simultaneously so that PAI learning can be an instrument for the formation of religious, inclusive, and national character academic personnel.